2022
DOI: 10.3389/fcvm.2022.837142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Excessive Activation of N-methyl-D-aspartic Acid Receptors in Neonatal Cardiac Mitochondrial Dysfunction Induced by Intrauterine Hypoxia

Abstract: Intrauterine hypoxia is a common complication during pregnancy and could increase the risk of cardiovascular disease in offspring. However, the underlying mechanism is controversial. Memantine, an NMDA receptor antagonist, is reported to be a potential cardio-protective agent. We hypothesized that antenatal memantine treatment could prevent heart injury in neonatal offspring exposed to intrauterine hypoxia. Pregnant rats were exposed to gestational hypoxia or antenatal memantine treatment during late pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(49 reference statements)
1
1
0
Order By: Relevance
“…Finally, NMDA-induced myocardial fibrosis, which may predispose ventricles to arrhythmias [ 57 ], can also by triggered by intracellular Ca 2+ overload. In accord, many reports have demonstrated that NMDAR stimulation can induce mitochondrial depolarization, reactive oxygen species (ROS) production, and caspase-3-mediated apoptosis in rat ventricular cardiomyocytes ( Figure 3 A) [ 46 , 47 ]. Similarly, NMDARs promoted Ca 2+ influx and Ca 2+ -dependent apoptosis by enhancing p38 MAPK activity in primary human neonatal cardiomyocytes cultured under ischemic conditions [ 65 ].…”
Section: Nmdar Expression Signaling and Function In The Heartsupporting
confidence: 59%
“…Finally, NMDA-induced myocardial fibrosis, which may predispose ventricles to arrhythmias [ 57 ], can also by triggered by intracellular Ca 2+ overload. In accord, many reports have demonstrated that NMDAR stimulation can induce mitochondrial depolarization, reactive oxygen species (ROS) production, and caspase-3-mediated apoptosis in rat ventricular cardiomyocytes ( Figure 3 A) [ 46 , 47 ]. Similarly, NMDARs promoted Ca 2+ influx and Ca 2+ -dependent apoptosis by enhancing p38 MAPK activity in primary human neonatal cardiomyocytes cultured under ischemic conditions [ 65 ].…”
Section: Nmdar Expression Signaling and Function In The Heartsupporting
confidence: 59%
“…Similarly, several studies had shown that hypoxia was closely related to the pathogenesis of CKD [42,43], stroke [14,44], cirrhosis, and other CLD [39]. During pregnancy, the mother or the baby is exposed to a hypoxic environment, which may affect the normal development of the child's brain [45,46], heart [47], or other organs [48], increasing the risk for the development of neonatal diseases [46]. Interestingly, our results showed that the age-standardized YLLs per 100,000 population of tracheal, bronchus, and lung cancers were significantly lower in the cluster of provinces with lower oxygen concentration (see Table 3), which seemed to conflict with the findings that hypoxia may have a general negative impact on the pulmonary system.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of oxidative stress, there is an elevation in mitochondrial ROS production, potentially resulting in oxidative impairment of the mitochondrial membrane. [ 42 ] This in turn influences energy generation and cellular functionality. The mitochondrial antioxidant enzyme system is a pivotal mechanism for shielding mitochondria against the harm induced by oxidative stress.…”
Section: Antioxidant Mechanismsmentioning
confidence: 99%